Screen-printed electrodes modified with carbon nanotubes or graphene for simultaneous determination of melatonin and serotonin - Gomez, Federico Jose Vicente (2015)
Single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT) and graphene have been tested as carbon allotropes for the modification of carbon screen-printed electrodes (CSPEs) to simultaneously determine melatonin (MT) and serotonin (5-HT). Two groups of CSPEs, both 4 mm in diameter, were explored: The first includes commercial SWCNT, MWCNT and graphene, the second includes SWCNT, MWCNT, graphene oxide nanoribbons and reduced nanoribbons that were drop casted on the electrodes. The carbon nanomaterials enhanced the electroactive area in the following order: CSPE <MWCNTs <SWCNTs <graphene. This allowed the simultaneous determination of 5-HT and MT at the working potentials of +50 mV and +390 mV (vs. Ag), respectively. The use of carbon nanomaterials, in particular of graphene oxide nanoribbons on CSPEs, represents an excellent and disposable tool for sensing the two target molecules in even small sample volumes. Figures of merit for MT and 5-HT include (a) detection limit of 1.1 and 0.4 μM for MT and 5-HT, respectively; (b) an inter-electrode reproducibility with RSD ≤ 8 %; (c) 120 s response time, and (d) recoveries (in case of spiked samples) ranging from 94 to 103 % (with an RSD < 1 %).